Pemberian Edukasi Berbasis Multimedia terhadap Kemampuan Perawatan Diri Pasien Kanker Kolorectal dengan Stoma - Retnoningrum, Dwi; Dahlia, Debie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of providing multimedia-based education on self-care of colorectal cancer patients with stomas. The research method used was a systematic review on four databases, namely Pubmed, Science Direct, ProQuest and Scopus with the keywords